Kleinia grandiflora (Asteraceae: Senecioneae), a species and genus newly discovered in Thailand - Vanijajiva, Ongkarn; Pornpongrungrueng, Pimwadee; Pongamornkul, Witthaya (Phytotaxa, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE TH MicrosoftInternetExplorer4 <![endif]–> Kleinia grandiflora (Wall. ex DC.) N.Rani has been recently found in a limestone mountain area of the northern part of Thailand. This represents a record new to Thailand not only of the species but also of the genus. In this study a new complete species description, a map of the species distribution in Thailand, original analytic line drawings, and photographs of this species are provided. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>